Discursive Presentation of Information in the Headlines of Modern French Newspapers - Jurayeva Maksouda (Research Parks Publishing LLC, 2022)
It should be noted that today most publications lack qualified design and pagination specialists. It's no secret that we need experienced photojournalists, professionals who work with websites and Internet resources. We'll explain in our article above. Plus, in this article we will talk about the basic principles of the article writing procedure, the rules of law. This knowledge will help you connect with the reader who is reading your article and present yourself as an expert. When writing the title of the article, it is emphasized that the main thing is not to overdo it and find a good solution.